Implementasi Pemberian Air Susu Ibu (ASI) Ekslusif - Derry Trisna Wahyuni (ARTERI : Jurnal Ilmu Kesehatan, 2021)
Early Breastfeeding have a fundamental role in the survival of infants. Colostrum is rich in antibodies, growth, health and infant nutrition.Reducing morbidity and mortality for infants and toddlers, Early Initiation of Breastfeeding (IMD) has an important role for mothers in stimulating uterine contractions so as to reduce postpartum bleeding (postpartum). Breastfeeding in the long term can extend the birth interval because the amenorrhea period is longer, better restoration of nutritional status before the next pregnancy.According to the National Social and Economic Survey (SUSENAS), coverage of exclusive breastfeeding in infants up to 6 months in 2007 ranges from 28.6%. Health Research Association (2010) shows the percentage of infants exclusively breastfed up to 6 months is only 15.3%. The purpose of this study is known implementation of the exclusive breastfeeding.This study uses qualitative methods. Qualitative data collection is done by interview 17 people and 7 FGD informants regarding the implementation of the exclusive breastfeeding is information dissemination, availability of access to information and education, monitoring and evaluationin Padang Panjang.Implementingtheholderin accordancewith the guidelinesof nutrition programsnutritional surveillance. As well as monitoringand evaluationis done oncea monthat the Posyandu, which is in linewithnutritionalguidelines for the surveillanceprogram.It will be require own policy regarding exclusive breastfeeding, allocate special funds to increase exclusive breastfeeding, optimization of lactation clinic or lactation corner on the and public health service, improve the ability of workers with technical training for facilitators and labor counseling counselor, and monitoring the implementation of the IMD and empower community to form a support group in breastfeeding. (jumlah kata abstrak Inggris menyesuaikan)